Incidence and management of mandibular fractures in a low-resource health facility in Ghana - Frimpong, Paul; Nguyen, Truc Thi Hoang; Sodnom-Ish, Buyanbileg; Nimatu, Edinam Salia; Dampare, Nana Yaa Asantewaa; Rockson, Roberta; Awuah, Samuel Baffour; Amponsah, Emmanuel Kofi; Newton, Cardinal; Kim, Soung Min (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2021)
The mandible and other parts of the maxillofacial region suffer significant morbid injuries following road traffic accidents. Our study gives epidemiological description of mandibular fractures in Ghana and also evaluates the relevance of closed reduction and indirect fixation for managing mandibular fractures in low-resource health facilities in low-income countries like Ghana. This is a retrospective study involving 268 patients who reported to the Department of Oral and Maxillofacial Surgery of the Sunyani Regional Hospital with mandibular fractures from January 2010 to December 2019. Patient medical records were assessed for information on age, sex, fracture etiology, anatomic location of fracture, time of day of road traffic accident, and other associated injuries. A total of 268 patients were included in this study (males, 216 [80.6%]; females, 52 [19.4%]). Motor vehicular accident (MVA) was the leading cause of mandibular fractures (202 injuries, 75.4%). Other etiologies included assault (39, 14.6%), gunshot (13, 4.9%), falls (12, 4.5%), and industrial accidents (2, 0.7%). Of the 161 male cases caused by MVA, 121 (75.2%) occurred at night and in the evening while the remaining 40 (24.8%) occurred in the morning and afternoon. Among all managed 222 patients, 212 (79.1%) were treated with closed reduction and indirect fixation technique while 10 (3.7%) were treated with open reduction and direct fixation. Closed reduction with indirect fixation could successfully be used to manage mandibular fractures in low resourced health facilities, especially in low-income countries. The poor lightening system on roads in Ghana is a major contributory factor to motor vehicular accidents.